Long COVID and the role of physical activity: a qualitative study. Issue 3 (10th March 2021) - Humphreys, Helen; Kilby, Laura; Kudiersky, Nik; Copeland, Robert
Abstract : Objectives: To explore the lived experience of long COVID with particular focus on the role of physical activity. Design: Qualitative study using semistructured interviews. Participants: 18 people living with long COVID (9 men, 9 women; aged between 18–74 years; 10 white British, 3 white Other, 3 Asian, 1 black, 1 mixed ethnicity) recruited via a UK-based research interest database for people with long COVID. Setting: Telephone interviews with 17 participants living in the UK and 1 participant living in the USA. Results: Four themes were generated. Theme 1 describes how participants struggled with drastically reduced physical function, compounded by the cognitive and psychological effects of long COVID. Theme 2 highlights challenges associated with finding and interpreting advice about physical activity that was appropriately tailored. Theme 3 describes individual approaches to managing symptoms including fatigue and 'brain fog' while trying to resume and maintain activities of daily living and other forms of exercise. Theme 4 illustrates the battle with self-concept to accept reduced function (even temporarily) and the fear of permanent reduction in physical and cognitive ability. Conclusions: This study provides insight into the challenges of managing physical activity alongside the extended symptoms associated with long COVID. Findings highlight the need for greater clarity and tailoring of physical activity-related advice for people with long COVID and improved support to resume activities important to individual well-being.